2016
DOI: 10.3390/rs8030268
|View full text |Cite
|
Sign up to set email alerts
|

Blending Satellite Observed, Model Simulated, and in Situ Measured Soil Moisture over Tibetan Plateau

Abstract: Abstract:The inter-comparison of different soil moisture (SM) products over the Tibetan Plateau (TP) reveals the inconsistency among different SM products, when compared to in situ measurement. It highlights the need to constrain the model simulated SM with the in situ measured data climatology. In this study, the in situ soil moisture networks, combined with the classification of climate zones over the TP, were used to produce the in situ measured SM climatology at the plateau scale. The generated TP scale in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 83 publications
2
84
0
Order By: Relevance
“…These can be used as additional quality scores of soil moisture time series. Several applications of TC to soil moisture time series have been published [43,[117][118][119][120][121][122][123][124][125][126][127]. Gruber et al [128] list the assumptions made to perform the TC analysis: (i) Linearity between the true soil moisture signal and the observations; (ii) signal and error stationarity; (iii) independency between the errors and the soil moisture signal (error orthogonality); and (iv) independency between the errors of three soil moisture time series (zero error cross-correlation).…”
Section: Description Of the Metrics Used For Validationmentioning
confidence: 99%
“…These can be used as additional quality scores of soil moisture time series. Several applications of TC to soil moisture time series have been published [43,[117][118][119][120][121][122][123][124][125][126][127]. Gruber et al [128] list the assumptions made to perform the TC analysis: (i) Linearity between the true soil moisture signal and the observations; (ii) signal and error stationarity; (iii) independency between the errors and the soil moisture signal (error orthogonality); and (iv) independency between the errors of three soil moisture time series (zero error cross-correlation).…”
Section: Description Of the Metrics Used For Validationmentioning
confidence: 99%
“…It is sensitive to climate change due to its unique geographical features and ecological environments [3]. Current studies have made great efforts to obtain the surface biogeophysical parameters in this region [38,39]. However, validation endeavours regarding satellite-based soil moisture products from the Tibetan Plateau reveal an unsatisfactory performance [2,[40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the ESA CCI soil moisture dataset is not suitable for the current study. The limited availability of satellite-based soil moisture estimates over the plateau within ESA CCI merged product mainly due to the inherent difficulties in retrieving soil moisture from permafrost and seasonally frozen ground [30]. Apparently, the ESA CCI soil moisture product is not suitable for the climate change studies at sub-continental and long-time scale due to the sparse retrieval of soil moisture over frozen land surfaces.…”
Section: Appendix a A Discussion On The Strengthening Trend Of Platementioning
confidence: 99%
“…Previous evaluations of several reanalysis data for China showed that the ERA-40 reanalysis might generally capture the inter-annual variations of soil moisture from the surface to deeper layers [27,28]. Reasonable performances for ECMWF soil moisture analyses in the humid monsoon period were found using in situ measurements over the plateau [29,30]. Liu et al [31] indicated that the ERA-Interim soil moisture has better performance over the plateau compared to the National Centers for Environmental Prediction (NCEP) Climate Forecast System Reanalysis (CFSR).…”
Section: Datamentioning
confidence: 99%